Microtitration of Rubella Virus in Monovalent Vaccinal Products - F Esna-Ashari; A Shafyi; M Taqavian; A Mohammadi; ZA Sadigh; GhH Sabiri; H Mirshahreza; Z Hamzehloo; F Taleblue; N Sheikh-Mohammadi (Tehran University of Medical Sciences, 2011)
Background: Potency test for control of rubella vaccine is a significant factor to qualify production line and vaccination program. For this reason, WHO recommends to use the microtitration method by both vaccine companies and control laboratories. Then the study was done to improve this test. Methods: Three rubella virus samples, including an in-house standard, a lot of vaccine and an in- process product, were tittered in cell culture tubes. Then micro titration steps were tested on 96-well microplate using cocultivation of standard rubella vaccine dilutions and RK- 13 cell line. After 6-7 days, final reading was done and calculated the titer. Two other samples were assayed with the micromethod. Results: Titer reduction less than 0.5 log was acquired for each sample during frequent tests and between two methods. Conclusion: The procedure was profitable and accurate for potency and identity tests of rubella virus vaccine, on the basis of WHO recommendations.